Intra-orogenic Svecofennian magmatism in SW Finland constrained by LA-MC-ICP-MS zircon dating and geochemistry - Vaisanen M; Eklund O; Lahaye Y; O'Brien H; Frojdo S; Hogdahl K; Lammi M (TAYLOR & FRANCIS LTD, 2022)
We have studied plutonic rocks from the Korpo and Rauma areas of south-western Finland which can be categorized as intra-orogenic, i.e. they were intruded during a proposed extensional period between the two main Svecofennian orogenic cycles: the Fennian and Svecobaltic orogenies. The diorite from Rauma yielded an age of 1865 +/- 9 Ma and the diorite from Korpo an age of 1852 +/- 4 Ma. The adjacent garnet-bearing Korpo granite was 1849 +/- 8 Ma in age. Zircons from the granite also included inherited Archaean and older Palaeoproterozic zircons, as well as metamorphic c. 1820 Ma rims. The diorites are high-K to shoshonitic, mantle-derived magmas, rich in Fe, P, F and light rare earth elements. The Korpo granites show typical features of crustal-derived melts and form hybrids with the diorites in contact zones. Both the mantle-derived and crustal-derived intra-orogenic magmatism are considered to have had a causal effect on the subsequent late Svecofennian (Svecobaltic) thermal evolution in southern Finland which culminated in granulite facies metamorphism and large-scale crustal melting.